Scintillation material on the basis of BaₓSr₁₋ₓI₂:Eu solid solutions - Rebrova, N.V.; Cherginets, N.N.; Ponomarenko, T.V.; Rebrova, T.P.; Vjunnik, I.N.; Zelenskaya, O.V.; Kosinov, N.N. (Functional Materials, 2009)
Single crystals of solid solutions Srl₂:Eu, Bal₂:Eu and BaₓSr₁₋ₓI₂:Eu with concentration of Eul₂ equal to 0.5 mol. % were grown by Bridgman-Stockbarger method. Addition of Bal₂ to Srl₂:Eu is found to cause arising two emission bands in the luminescence spectrum. One of them with maximum ea 430 nm is usual for Eu-containing halides, another with maximum at wavelength in 550-580 nm range is characterized by the shift of maximum position at varying Bal₂ concentration. The latter band arising is explained by distortions of crystal lattice of solid solution as compared with that of Bal₂ or Srl₂ since Sr²⁺ and Eu²⁺ from the one hand and Ba²⁺ from the other one have appreciably different radii. As a result, the light yield for the obtained materials decreases and the energy resolution deteriorates.